Salient considerations to address forage seeds access and use in eastern Africa - Mwendia, Solomon; Burkart, Stefan; Notenbaert, An; Peters, Michael (2024)
While the primary obstacles to enhancing ruminant productivity in eastern Africa are well-documented, practical measures to address them are imperative. In this study, we focused on enhancing access to forage seeds for cultivation in cattle systems in several eastern African countries, namely Ethiopia, Tanzania, Kenya, Uganda, Rwanda, and Burundi. Drawing from existing literature, we examined factors such as ruminant population, feed dry matter deficits, and governmental priorities concerning cattle. The lack of access to forage seeds, coupled with a reluctance to invest in what is perceived as expensive elite improved forages, poses a significant challenge. Many farmers rely on vegetative planting materials, often utilising outdated improved materials that have not been adequately maintained for purity. Our analysis indicates a pressing need to transition to recently improved materials through rigorous selection and breeding processes to ensure sustained quality. To address the perceived high cost of seeds, there is a critical need to explore domestic seed production within the continent rather than relying on imports, which incur additional transport costs and other logistic and administrative burdens, such as complex variety registration processes. Given the nascent stage of the forage seed market in Africa, coordinated seed production efforts targeting a pooled market across multiple countries would be more economically viable than individual national initiatives. The development of such market would help fostering adoption levels of improved forages and promises a triple-win scenario, offering increased productivity, environmental benefits (including reduced methane production intensity), and alignment with the regional governments' ambitious agendas for the sector.